KNOWLEDGE, AWARENESS AND PERCEPTION TOWARDS PROSTATE CANCER AMONG MALE PUBLIC STAFFS IN KELANTAN - Hafiz M.S., Muhammad Fadhil; L.K., Soon; Y., Azlina (2016)
Background: In Malaysia, prostate cancer is the fourth most common cancer among men. Its incidence is rising due to the aging population. Assessing knowledge and awareness of prostate cancer are necessary to promote screening behavior for early detection of prostate cancer. The aim of this study was to determine levels of knowledge, awareness and perceptions of prostate cancer among male staffs in a tertiary teaching hospital in Kelantan. Materials and Methods: A cross-sectional study using purposive sampling technique was conducted from December 2014 to January 2015. A structured questionnaire was administered to eighty participants. Descriptive statistics was used to summarize socio-demographic and medical characteristics of the participants. Pearson Chi-Square analyses were conducted to explore the association between knowledge, awareness, and perception and socio-demographic data. Result: Fifty-two participants (65.0%) reported having heard about prostate cancer but the majority (n=55, 68.8%) have a low level of knowledge and awareness about it. Of the participants, 63 (78.8%) do not know the factors that make a person more likely to get prostate cancer. Although there is no significant association between socio-demographic characteristics and knowledge, awareness, and perception but majority (n=76, 95%) has a good perception of susceptibility, seriousness and benefit to prostate cancer. Conclusion: This study revealed that knowledge and awareness of prostate cancer among these male staffs was low. The findings of the present study indicate needs for health promotion on prostate cancer and screening program to improve public understanding and acceptance for early prostate cancer screening.